Young people practicing martial arts and their perception of success - W.J. Cynarski; P. Pawelec; J.-H. Yu; J. Slopecki; G. Bielec; K. Kubala (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Background: The scientific framework for this study is the Humanistic Theory of Martial Arts that provides the specific language and definitions for Combat Sports/Martial Arts manifestations. Objective: The main aim was to describe the "perception of success" in groups in age 15-17, 11,11% girls and 88,89% boys involved in martial arts training. Participants ( n = 63) consisted of young martial artists from Poland and the United States. Methods: The instrument used for data collection was the Perception of Success Questionnaire (POSQ) (translated into Polish); Statistical analysis consisted of calculating the Spearman rank correlation for each pair of subgroups being analyzed a Coefficient of variation for comparison between the values of measurement. Results: 1) A weak correlation between the type of cultivated fighting style and the perceptions of success (Spearman rank correlation = ,35); 2) A moderate relationship between the US participants versus the Polish participants, and the perceptions of success (Spearman rank = ,69); and 3) A weak relationship between sex (as a gender) and the perceptions of success in the martial arts and combat sports (Spearman rank = ,34). Conclusions: This study concludes that the form or style of cultivated martial art or combat sport being practiced did not have a significant impact on the perception of success expressed by children and young people engaged in it.